(untitled) (JURNAL GEOCELEBES, 2022)
Granite in Lampung Province is widely exposed but not much has been discussed so that it is still causing debate, especially in the context of the tectonic episode of its formation. This study aims to reconstructed formation of the Lampung granitoid in a tectonostratigraphic framework. The research was carried out by mapping the field in four places, Tanjung Bintang, Branti, Padean, and Tarahan to reconstructed genesis of granitoid formation using a tectonic approach based on the order of rock age. This study shows that the Lampung granitoids can be divided into three different tectonostratigraphy, are subduction related granitoids, collision-delamination granitoids, and post-orogrnic granitoids. Subduction related granitoids characterized by granitoid to tonalite lithology that cross cutting metamorphic rocks. Collision-delamination related granitoids are characterized by migmatite to leucogranite and foliated granodiorite. Post-orogenic collapse granitoids characterized by microgranite associated with mafic-intermediet rock such as basalt, diabas, and andesite.